Pro Windows PowerShell - Deshev, Hristo (Berkeley, CA ; New York, NY : Apress, 2008)
A guide to using Windows PowerShell to script Windows administrative tasks and control Windows from the command line.
Includes index.
Keywords: Microsoft Windows (Computer file); Microsoft Windows (Computer software); Operating systems (Computers); Computer operating systems